2016
DOI: 10.5127/jep.048115
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance of Uncertainty Mediates the Relationship between Panic and the Startle Reflex in Anticipation of Unpredictable Threat

Abstract: The present study examined whether intolerance of uncertainty (IU) was associated with the startle reflex in anticipation of unpredictable threat, and whether IU mediated the relationship between panic and sensitivity to unpredictable threat. This was tested in separate samples of 86 undergraduates with varying panic symptoms and 148 adults with current panic disorder or no lifetime history of an anxiety disorder. Participants completed the Intolerance of Uncertainty Scale, which measures cognitive distress (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 68 publications
(89 reference statements)
4
13
1
Order By: Relevance
“…Nelson et al (2014) also found that the P-IU subscale, but not the I-IU subscale, was associated with reduced approach motivation and mediated the association between depression and approach motivation during reward. Other studies have found similar results in which P-IU was uniquely associated with diminished reward or exaggerated threat responding (Jackson et al, 2016;Nelson et al, 2016). However, two studies have had slightly different results.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Nelson et al (2014) also found that the P-IU subscale, but not the I-IU subscale, was associated with reduced approach motivation and mediated the association between depression and approach motivation during reward. Other studies have found similar results in which P-IU was uniquely associated with diminished reward or exaggerated threat responding (Jackson et al, 2016;Nelson et al, 2016). However, two studies have had slightly different results.…”
Section: Discussionsupporting
confidence: 61%
“…P-IU and I-IU were then entered as simultaneous independent variables, which allows for examination of each IU subscale while controlling for the other. Of note, several recent studies have suggested that the two IU subscales should be entered into statistical models simultaneously to prevent potential mutual suppressor effects in which two correlated predictor variables have the opposite effect on the criterion/ outcome variable, causing the associations to be obscured when each subscale is examined separately (Jackson et al, 2016;Nelson et al, 2016;Watson, Clark, Chmielewski, & Kotov, 2013).…”
Section: Fmri Processing and Analysesmentioning
confidence: 99%
“…These results indicate the presence of mutual suppressor effects, when two correlated predictor variables have the opposite effect on a criterion variable, but the associations are obscured when examined separately (MacKinnon et al, 2000; Watson et al, 2013). The suppressor effect finding is not particularly surprising as other symptom dimensions have demonstrated similar effects in relation to psychophysiological measures of threat and reward sensitivity (Jackson, Nelson, & Hajcak, 2016; Nelson, Kessel, Jackson, & Hajcak, 2016; Nelson, Liu, Sarapas, & Shankman, in press). Together, these results highlight the importance of considering the multidimensional nature of anxiety and depression when examining potential underlying mechanisms.…”
Section: Discussionmentioning
confidence: 68%
“…Prospective IU has been particularly associated with GAD , a condition characterized by increased positive and negative emotional reactivity and poor emotion regulation (Mennin, Turk, Heimberg, & Carmin, 2004). Indeed, in a separate investigation, greater prospective IU was associated with an increased startle reflex in anticipation of unpredictable threat (Nelson et al, 2015). These results suggest that, in contrast to inhibitory IU, high prospective IU is associated with increased psychophysiological reactivity to appetitive and aversive stimuli.…”
Section: Discussionmentioning
confidence: 74%
“…A number of studies have identified distinct relationships between inhibitory and prospective IU and psychobiological responding to uncertainty. For example, inhibitory IU has been associated with a decreased startle reflex while anticipating uncertain threat (Nelson & Shankman, 2011) and an attenuated ERN (Jackson, Nelson, & Hajcak, 2015b), whereas prospective IU has been associated with an increased startle reflex while anticipating uncertain threat (Nelson, Liu, Sarapas, & Shankman, 2015) and an enhanced ERN (Jackson et al, 2015b). Therefore, as an exploratory analysis, we examined whether there were specific relationships between the inhibitory and prospective IU subscales and the RewP.…”
mentioning
confidence: 99%